2018
DOI: 10.4315/0362-028x.jfp-17-464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Environmental Monitoring Program for the Microbial Safety of Air and Surfaces in a Dairy Plant Environment

Abstract: Microbiological hazards can occur when foodstuffs come into contact with contaminated surfaces or infectious agents dispersed by air currents in the manufacturing environment. An environmental monitoring program (EMP) is a critical aspect of sustainable and safe food manufacturing used to evaluate the effectiveness of the microbial controls in place. An effective EMP should be based on risk analysis, taking into account previous sampling history to determine the selection of the sampling points, the scope of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…Overall, our data indicate that these were a significant reduction in the microorganism after the implementation of the EMP system. This is similar to findings by Zacharski et al (2018) that reported an environmental monitoring program plays an important role in the control of microbiological hazards in a dairy plant environment.…”
Section: Resultssupporting
confidence: 91%
“…Overall, our data indicate that these were a significant reduction in the microorganism after the implementation of the EMP system. This is similar to findings by Zacharski et al (2018) that reported an environmental monitoring program plays an important role in the control of microbiological hazards in a dairy plant environment.…”
Section: Resultssupporting
confidence: 91%
“…Each step along the milk processing train can be contaminate by the air [74] and the water [75], used in the milk processing stages. Hygiene control at all stages, including hygienic design of the manufacturing equipment, is critically important.…”
Section: Microbiological Quality Analysesmentioning
confidence: 99%
“…The adaptation and survival of L. monocytogenes in the food processing facilities occur mainly through their ability to proliferate in low temperature, pH and osmotic stress (Takahashi et al, 2014), as well as resistance to sanitation agents and formation of biofilm (Hurley et al, 2019). The control of L. monocytogenes in the food processing facilities is mostly based on application of quaternary ammonium compounds (QACs) biocides, such as BCs (Zacharski et al, 2018;Maury et al, 2019). However, the evolution of L. monocytogenes resistant to the BCs has been reported in several studies and has become a serious global concern (Zacharski et al, 2018;Korsak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The control of L. monocytogenes in the food processing facilities is mostly based on application of quaternary ammonium compounds (QACs) biocides, such as BCs (Zacharski et al, 2018;Maury et al, 2019). However, the evolution of L. monocytogenes resistant to the BCs has been reported in several studies and has become a serious global concern (Zacharski et al, 2018;Korsak et al, 2019). These BC resistances are associated with several efflux resistance genes including bcrABC cassette, Ide, mdrL, qacH, qacA, qacE 1sul, and emrE which have been reported in various serotypes, ST and CC of L. monocytogenes isolated from diverse sources (Kovacevic et al, 2016;Korsak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%